2007
DOI: 10.1074/jbc.m703894200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Dominant Negative Mutant of Bacillus subtilis GTP-binding Protein, YlqF, Essential for Biogenesis and Maintenance of the 50 S Ribosomal Subunit

Abstract: The circularly permuted GTPase YlqF is essential for cell viability and is broadly conserved from Gram-positive bacteria to eukaryotes. We previously reported that YlqF participates in the late step of 50 S ribosomal subunit assembly in Bacillus subtilis. Here, we demonstrate that an N-terminal deletion mutant of YlqF (YlqF⌬N10) inhibits cell growth even in the presence of wild-type YlqF. In contrast to the wild-type protein, the GTPase activity of this mutant was not stimulated by the 50 S subunit and did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…RbgA/YlqF is an essential GTPase required for the proliferation of B. subtilis (36,37). Depletion of RbgA or expression of a dominant-negative mutant of RbgA resulted in accumulation of the 45S particles (36)(37)(38)(39). However, unlike the E. coli 45S precursor, the B. subtilis 45S particle does not alter its sedimentation coefficient, even at 10 mM Mg 2+ (36,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RbgA/YlqF is an essential GTPase required for the proliferation of B. subtilis (36,37). Depletion of RbgA or expression of a dominant-negative mutant of RbgA resulted in accumulation of the 45S particles (36)(37)(38)(39). However, unlike the E. coli 45S precursor, the B. subtilis 45S particle does not alter its sedimentation coefficient, even at 10 mM Mg 2+ (36,39).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of RbgA or expression of a dominant-negative mutant of RbgA resulted in accumulation of the 45S particles (36)(37)(38)(39). However, unlike the E. coli 45S precursor, the B. subtilis 45S particle does not alter its sedimentation coefficient, even at 10 mM Mg 2+ (36,39). In addition, there is no homolog of RbgA in E. coli (10), and no homolog of RlmE in B. subtilis; consistent with this knowledge, U2552 in 23S rRNA remains unmethylated in B. subtilis (40).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that the equivalent segment in B. subtilis YlqF (Fig. S6), another circularly permutated GTPase involved in the 50S subunit assembly (27), is important in the nucleotide modulation of the binding of YlqF to the 50S subunit (28).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that OsNug2 is a GTP/GDP-binding protein that is comparable with that of other YawG subfamily proteins. Interestingly, a few recent studies have shown that some GTPases play important roles in the ribosomal maturation process and that their GTPase activities are enhanced in the presence of ribosomal subunits in vitro (21,25,48). In light of these observations, we measured the kinetic parameters of OsNug2 hydrolytic activity in the presence 40S, 60S, or the 80S ribosome purified from rice.…”
Section: Ubiquitous Expression Of Two Plant Nug2 Genes Belonging To Tmentioning
confidence: 99%